Optical Properties of Zn-based Semiconductor Nanoparticles and Application in Two-barcode Encryption - Quynh, Luu Manh; Huy, Hoang Van; Nam, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics; Vol 31 No 4, 2015)
Mn-doped ZnS (ZnS/Mn) nanoparticles synthesized by sono-chemical co-precipitation are combined with ZnO nanoparticles synthesized by sol-gel method for application in two-barcode encryption. Nanoparticles are mixed together in different mass proportions of ZnO: ZnS/Mn respectively being 5: 1, 10: 1, 15: 1, 20: 1, 25: 1.30 : 1 and 35: 1, before being pressed in 1 cm diameter, 1 mm thick KBr pellets. The photoluminescence (PL) of the tablet shows that the mass proportion of two materials could be distinghuished by the proportion of the PL intensities at 515 nm and 600 nm, which promises potential manufacturing ability two-substant/two-barcode information storage systems for civil security applications. Keywords: Photoluminescent encryption, Zn-based semiconductor, civil application.